Mediating Effects of Global Negative Effect Expectancies on the Association between Problematic Cannabis Use and Social Anxiety - Di Blasi, Maria; Cavani, Paola; Pavia, Laura; Tosto, Crispino; La Grutta, Sabina; Lo Baido, Rosa; Giordano, Cecilia; Schimmenti, Adriano (Frontiers in Psychiatry, 2017)
The relationship between social anxiety and cannabis use among adolescents and young adults is a highly debated topic. In this cross-sectional study, we tested whether cannabis use expectancies mediated the association between social anxiety and cannabis use severity in a sample of 343 young adults (74.3% male) who used cannabis. They completed self-report measures for the screening of problematic cannabis use (Cannabis Use Problems Identification Test) and social anxiety symptoms (Social Interaction Anxiety Scale and Social Phobia Scale). A multiple mediation analysis was used to test whether marijuana effect expectancies mediate social anxiety effect on problematic cannabis use. Social anxiety was negatively associated with cannabis use severity in this sample, and we found evidence that cannabis use expectancies fully mediated this relationship. Specifically, global negative effect expectancies influence the relationships between social anxiety and problematic cannabis use. These findings may inform current prevention strategies and clinical intervention for young adults who use cannabis.